The Impact Of Lockdown On Internet Searches Related To Alcohol Use (International Journal of Food and Nutritional Sciences, 2022)
Introduction - The COVID-19 pandemic has had a significant impact on everyday functioning, considerable measures being taken to reduce the spread of the virus.For many people, alcohol is part of their social life, a life that has been significantly disrupted by COVID 19. Currently however, it is uncertain what impact the COVID-19 pandemic will have on alcohol consumption, though they are likely mediated by psychosocial factors such as social isolation, grief and anxiety. Moreover, the lockdown yield a significant increase in the use of various internet sources for seeking information on a wide range of topics. Hence the present study design to examine and interpret the changes in online search interest for keywords representing different alcohol related themes during the lockdown period. Methods – The study was designed as a descriptive study.Internet search trends were compared before (1st May, 2021 to 10th May, 2021) and after the lockdown was imposed (11th May, 2021 to 24th May, 2021) in Tamil Nadu and Pondicherry. Google trends were utilized to give normalized relative search volume for online searches in its search engine. Results and conclusion - A substantial rise in internet search interest for terms linked to the purchase of alcohol was noticed in during lockdown, compared with pre‐lockdown.Indian individuals with access to the internet utilized search keywords linked to alternative means of acquiring alcoholand problems experienced due to break in alcohol supply chain during the lockdown.